SISTEM PERSAMAAN LINEAR DUA VARIABEL : DITINJAU DARI ANALISIS KESALAHAN SISWA MTs KELAS VIII PADA PEMBELAJARAN DARING - Diana Diana; Nelly Fitriani; Risma Amelia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze the location of the errors experienced by MTs students in solving the Two Variable Linear Equation System (SPLDV) questions in online learning. This study uses a qualitative descriptive method. The subjects are students of class IX in Karawang totaling 16 people. Data collection is done by analyzing 5 items of description. The problem indicators used are (1) Creating SPLDV as a mathematical model of the given situation, (2) Creating a mathematical model and determining the completion of SPLDV using the graphical method, (3) Creating a mathematical model and determining the completion of the SPLDV using the elimination method, (4) Making mathematical model and determine the solution of SPLDV by substitution method, (5) Identifying special SPLDV and its solution. Based on the results of the study, the highest student errors were found in the indicators of making mathematical models and determining the completion of the SPLDV using the graphical method with an error percentage of 87.5% (where the minimum criteria were 75%). Based on the results of the analysis, the factors that make these indicators experience errors are that students have difficulty in transforming story questions into the form of mathematical models and difficulties when drawing graphs, this happens because during online learning the concept construction process and the form of visualization when constructing concepts are very difficult to facilitate.